Design of an universal source for semi-automatic ac welding and induction heating - Burlaka, Vladimir; Lavrova, Elena; Podnebennaya, Svetlana; Ivanov, Vitaliy; Burikov, Serhii (Eastern-European Journal of Enterprise Technologies, 2021)
This paper proposes a circuit solution and a power source control algorithm for semi-automatic AC welding with improved energy and weight-size characteristics. A distinctive feature of the designed source is the absence of an input rectifier: welding is carried out with a high-frequency alternating current. That has made it possible to significantly reduce power losses in the source, as well as provide the possibility of implementing induction heating by connecting an inductor to the source output. Another distinctive feature of the designed source is an increased power factor and a reduced level of higher harmonics of the current consumed. The power factor of the described source reaches 0.94 against 0.5÷0.7 for sources equipped with a conventional rectifier with capacitive smoothing. The designed source’s composition includes a power supply system for the wire feed drive with speed stabilization due to positive feedback on the motor current. That has made it possible to ensure the stable operation of the drive in a wide range of speeds. A model has also been developed of a flux wire welding torch containing a feed drive and a coil with a wire (up to 100 mm in diameter), placed, in order to reduce the size, in the handle of the torch. In addition to the welding function, the source makes it possible to solve the tasks related to induction heating and/or hardening of small parts; to that end, a compact inductor is connected to its output. Tests of the source showed the feasibility of the proposed ideas and circuit solutions. The dimensions of the source are 190×107×65 mm; weight, 1.4 kg; output current, up to 120 A. The proposed technical solution enables the construction of small-sized, lightweight, universal, easy-to-use power supplies for semi-automatic welding with the option of induction heating